2019
DOI: 10.1093/ofid/ofz180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culturing the Organ Preservation Fluid on Solid Organ Transplantation: A Prospective Multicenter Cohort Study

Abstract: Background We analyzed the prevalence, etiology, and risk factors of culture-positive preservation fluid and their impact on the management of solid organ transplant recipients. Methods From July 2015 to March 2017, 622 episodes of adult solid organ transplants at 7 university hospitals in Spain were prospectively included in the study. Results The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 26 publications
0
54
3
1
Order By: Relevance
“…However, a study by Oriol et al showed that pre-emptive therapy with high-risk preservation fluid contamination (defined as isolation of Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. and/or Candida species) led to a decrease in the rate of infections [96]. In the cohort with contaminated high-risk preservation fluid with pre-emptive therapy, no complications were found versus a rate of 8.5% complications in the contaminated high-risk group without pre-emptive therapy.…”
Section: Donor-derived Candida Infectionsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, a study by Oriol et al showed that pre-emptive therapy with high-risk preservation fluid contamination (defined as isolation of Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. and/or Candida species) led to a decrease in the rate of infections [96]. In the cohort with contaminated high-risk preservation fluid with pre-emptive therapy, no complications were found versus a rate of 8.5% complications in the contaminated high-risk group without pre-emptive therapy.…”
Section: Donor-derived Candida Infectionsmentioning
confidence: 84%
“…Many of these infections are presumed to be secondary to preservation fluid contamination, which can occur prior to or at the time of organ procurement. The rates of preservation fluid contamination range from 9.5% up to 37%, although of those specifically due to Candida species range from 0.6% up to 4.1% [91][92][93][94][95][96]. C. albicans remains the most common species identified ranging from 25% up to 64% of all cases [93,95,96].…”
Section: Donor-derived Candida Infectionsmentioning
confidence: 99%
“…Microbiological culture of perfusion fluids was performed in almost all cases. A recent nationwide study from France concluded that 24% of deceased donor perfusion fluid cultures were positive, while a multi‐center cohort study from Spain reported a prevalence of 62.5% . A previous study in our institution between 2007 and 2011 identified an overall perfusion fluid contamination rate of 7.2%, similar to the rates observed in 2014 and 2016 (9%).…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, a presença de microrganismos na cultura do LP tem sido apontada como importante causa de infecções e mortalidade pós transplante, favorecidas pela imunossupressão desses pacientes, e embora tenha sido frequentemente atribuída ao órgão doado, especula-se que o mecanismo de contaminação ocorra nos processos entre a retirada do órgão do doador e a implantação no receptor (4). Tendo isso em vista, alguns centros de transplante realizam culturas intraoperatórias do LP para detectar a contaminação do órgão e melhorar o diagnóstico precoce e manejo de complicações relacionadas à infecção (4,5).…”
Section: Introductionunclassified